2021
DOI: 10.1002/bit.28002
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent self‐control of carbon metabolic flux in SecY‐engineered Escherichia coli for xylitol biosynthesis from xylose‐glucose mixtures

Abstract: Xylitol is a salutary sugar substitute that has been widely used in the food, pharmaceutical, and chemical industries. Co-fermentation of xylose and glucose by metabolically engineered cell factories is a promising alternative to chemical hydrogenation of xylose for commercial production of xylitol. Here, we engineered a mutant of SecY proteintranslocation channel (SecY [ΔP]) in xylitol-producing Escherichia coli JM109 (DE3) as a passageway for xylose uptake. It was found that SecY (ΔP) channel could rapidly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Cofermentation of glucose and xylose has been investigated widely to utilize the two main lignocellulosic monosaccharide simultaneously and avoid tedious separation (Kim et al 2022). Efforts of metabolic engineering has been taken to promote the utilization of xylose when the obstacle of CCR is severe, especially on the enhancement of xylose uptake channel (Fox and Prather 2020; Guo et al 2022). In this study, the rapid consumption of glucose before xylose indicated signi cant CCR.…”
Section: Comparison Of Glucose and Xylose Fermentationmentioning
confidence: 74%
“…Cofermentation of glucose and xylose has been investigated widely to utilize the two main lignocellulosic monosaccharide simultaneously and avoid tedious separation (Kim et al 2022). Efforts of metabolic engineering has been taken to promote the utilization of xylose when the obstacle of CCR is severe, especially on the enhancement of xylose uptake channel (Fox and Prather 2020; Guo et al 2022). In this study, the rapid consumption of glucose before xylose indicated signi cant CCR.…”
Section: Comparison Of Glucose and Xylose Fermentationmentioning
confidence: 74%
“…Kasari et al (2022) induced the removal of oriC from the chromosome of Escherichia coli by a site‐specific serine recombinase, which stopped cell growth and was coupled to recombinant protein expression. Ideally, growth decupling schemes could be combined with the autonomous induction of protein expression by environmental factors like carbon source (C‐source) (Bothfeld et al, 2017; Guo et al, 2022; Strittmatter, Egli, et al, 2021), shear rate (Strittmatter, Argast, et al, 2021), or dissolved gases (Werner et al, 2007) in high‐cell density cultures. Attaining high cell‐densities in batch mode remains a challenge, due to metabolic and physical constraints.…”
Section: Introductionmentioning
confidence: 99%
“…D-Xylose is the second largest monosaccharide content in lignocellulosic hydrolysates, 20 and there has been a high interest in utilizing D-xylose in microbial fermentation for chemical production. 21 D-Xylose is transported to the cytoplasm by xylose transporters (XylFGH and XylE) 22 and then enters the pentose phosphate (PP) pathway to generate glyceraldehyde-3-phosphate (G-3-P) and F-6-P. 23 In our previous study, an engineered E. coli using a D-xylose− methanol mixture for D-allulose production was constructed by coexpressing AlsE, A6PP, methanol dehydrogenase (Mdh), hexulose phosphate synthase (Hps), phosphohexose isomerase (Phi) and deleting ribose-5-phosphate isomerase A (RpiA), 6phosphofructokinase isozyme A (PfkA), 6-phosphofructokinase isozyme B (PfkB), and formaldehyde detoxification operon (FrmRAB). 24 This is a great example of promoting the use of C5 and C1 substrates for synthesizing C6 products in the biochemical industry.…”
Section: ■ Introductionmentioning
confidence: 99%